Examining the Role of a Structured Seminar Course in Developing Research Readiness of Pre-Service Physics Teachers - Taufik, Muhammad; Hikmawati,; Ahmadi,; Khery, Yusran (Hydrogen: Jurnal Kependidikan Kimia, 2025)
The training of preservice physics teachers to participate in educational research is a long-standing issue in physics teacher education. This investigation seeks to understand the effectiveness of a focused seminar course in facilitating research readiness across time and by performance-based assessment and analysis of a research portfolio. Twenty-six preservice physics education students attended a semester-long seminar course focusing on research problem identification, critical response to SINTA and Scopus indexed journals articles, proposal development, and academic communication. The growth in students’ development was studied using a phase-based analysis between the weekly assessment based on a Research Task Plan (RTM) and qualitative analysis of research portfolios. The answers provide evidence of a continuous development of students’ research competencies with less variation in performance over the course levels. Analysis of the portfolios also suggests a shift away from mostly descriptive engagement with research literature toward more critical and comparative disciplinary analysis. These results indicate that seminars, designed as scaffolded learning environments that are authentic can be pedagogically effective in bridging between coursework taken by undergraduates and research done independently especially in the context of physics teacher preparation.